The effect of short game videos on consumers' willingness to purchase virtual items in games: A moderating effect based on game experience - Wu, Hongfei; Gao, Ruizhe; Yin, Yitong (Journal of Asian Business Strategy, 2024)
With the popularity and development of new media, the short video industry has deeply influenced people's daily shopping behavior and entertainment activities. Similarly, with the development of Internet technology, the game industry is attracting more and more attention from game players and consumers. This study explores the impact of short game videos on gamers' willingness to purchase in-game virtual goods according to the SOR theoretical model and the moderating effect of external stimuli such as consumers' differences in game experience and perceived value on their willingness to buy game virtual products. Through a series of literature research and relevant data analysis and processing, this study confirms that some features of short game videos will not have a significant impact on consumers' purchase behavior, but most features will lead consumers to consume games. Features such as Validity and Serviceability, Interactivity, and Sociability are positively correlated with consumers' willingness on consumption, but Influenceability is not significantly correlated with consumers' willingness to buy. In addition, the game experience of consumers has a significant moderating effect, and the perceived value difference also has an important impact on their purchase behavior. The findings from this study can help the new media industry and the gaming industry to grasp the needs of young consumers, represented by university students, and to adjust their marketing strategies more effectively.